Female Arab International Students Negotiate Their Identities - Hassan, Sinaria (Journal of International Students, 2025)
This study examines the identity negotiation of Muslim female international students in ESL classrooms in the mid-southern United States, where linguistic adaptation and cultural integration pressures intersect. Drawing on intersectionality, postcolonial feminism, and Kim’s International Student Identity Model, this research highlights how these students navigate religious, gendered, and cultural expectations within Western academic settings. A qualitative methodology utilizing semi-structured interviews with six participants revealed key themes: cultural and religious identity adaptation, experiences of discrimination, and resilience strategies. Participants described the dual pressure of conforming to Western norms while upholding Islamic practices, such as wearing the hijab and adhering to halal dietary restrictions. Findings underscore the need for inclusive ESL pedagogies that integrate cultural competency training, peer mentorship programs, and institutional policy reforms. By fostering an equitable learning environment, institutions can enhance cross-cultural understanding and student well-being. This research contributes to scholarship on international student adaptation and identity-affirming educational spaces.